PP63 Factors Influencing Drug Prices Among Philippine Public Hospitals - Wong, John (Archīum Ateneo, 2019)
Introduction:In the Philippines, medicines are procured at higher rates in government hospitals. The prices of essential medicines have high variability, and a significant portion of out-of-pocket expenditures by Filipinos is for medicines. This study's objective is to determine the factors associated with the variation in drug pricing among public hospitals. Methods:This was a mixed-methods, case-control study of 57 hospitals. Two tools were developed based on: (i) Management Sciences for Health (MSH)’s Rapid Pharmaceutical Management Assessment and (ii) World Health Organization (WHO)’s Good Pharmaceutical Practices. The dependent variable is a drug price reference ratio of a preselected drug basket. Examples of factors studied are: (i) preference for generics, (ii) procurement type, and (iii) time out of stock. Results:Hospitals with proper procurement planning and performance monitoring are expected to decrease the price ratio (R = -0.030). However, interview data showed that forecasting is still not robust enough. Past consumption (91 percent) remained the most frequently used input to procurement planning. Few hospitals took into consideration other factors such as morbidity, mortality, and patient demographics. The expertise of hospital procurement staff increases the hospital's price mark-up. Interview results suggest this is because members and hospital units do not meet eye-to-eye to ensure accountability and coordination across units in planning and implementing the procurement procedures. Conclusions:By having a forward-looking procurement plan, forecasting can be more efficient. Potential improvement lies in finding mechanisms where nearby hospitals could participate in pooled procurement. Pooled procurement could have an impact on reducing prices by capturing economies of scale, provided this is operated efficiently and transparently.